Therapeutic Uses and Efficacy of Botulinum Toxin in Orofacial Medicine (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
In recent years, the applications of botulinum toxin therapy have expanded explosively, including for diseases of the oral region. The aim of the following reprint is to provide a summary of the current status and the latest information on botulinum toxin therapy for various diseases of the stomatognathic system, focusing on specialists in each field, especially dentists and oral surgeons who are experts in botulinum toxin therapy. The following reprint covers a wide range of topics, including neurological conditions such as oromandibular dystonia, pain-related disorders such as myofascial pain, primary headache, trigeminal or post-herpetic neuralgia, diseases of the temporomandibular joint such as temporomandibular joint disorder and bruxism, sialorrhea, and also minor cosmetic applications. Neurological conditions and pain-related disorders require collaboration between medicine and dentistry, and this point is also discussed. We believe that this reprint will be of interest to many readers in other fields, including dentists and physicians.